MENGOPTIMALKAN PEMBELAJARAN MEMBACA PERMULAAN PADA ANAK DISLEKSIA MELALUI METODE NON-EJA - Yeni Sulistyaningrum; Mochamad Nursalim (Program Studi Pendidikan Guru Sekolah Dasar FKIP Universitas Pasundan, 2025)
This study aims to explore the implementation of the no-spelling reading method in improving early reading skills in children with dyslexia at SDN Sogo 02, Balerejo District, Madiun Regency. This research uses a descriptive qualitative approach involving 7 dyslexic children from grades 1 and 2. Data were collected through observation, unstructured interviews, and document studies. The results show that before the implementation of the no-spelling reading method, 2 children did not recognize the alphabet, and 5 other children were only able to read syllables with a CV (Consonant-Vowel) pattern. After intensive application of this method, significant improvement was observed. The 2 children who previously did not recognize letters were able to read syllables with the CV pattern, 2 others could read words with CV-CV and CV-CVC patterns, while 3 other children became fluent in reading syllables with the CVC pattern. The no-spelling reading method proved to be effective in improving the early reading abilities of children with dyslexia and can be an alternative teaching method that suits the characteristics of these children.